Multi-Stakeholder Media Provenance Management to Counter Synthetic Media Risks in News Publishing - Aythora, J.; Burke‐Agüero, R.; Chamayou, Amaury; Clebsch, Sylvan; Costa, Manuel; Earnshaw, N.; Ellis, L.; England, Paul; Fournet, Cédric; Gaylor, M.; Halford, C.; Horvitz, Eric; et al. (International Broadcasting Convention (IBC), 2020)
The rise of indirect content distribution via third party social media platforms has introduced a new conduit for synthetic or manipulated content. That content purports to be legitimate news, or to come from legitimate news sources, and can present the consumer with apparent brand integrity markings, which convey authority. Three major global news organizations and a leading technology provider have come together to demonstrate a mechanism to tackle this problem that can operate at scale. The BBC, The New York Times Company, and CBC/Radio‐Canada in cooperation with Microsoft have developed a proposed open standards approach which can be used by large and small news organizations to protect the provenance of news stories in audio/visual/textual media.